THE EFFECT OF WORK MOTIVATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS MEDIATION AT FIFGROUP DENPASAR - I Gusti Ngurah Made Wedahana Putra; Nengah Suardhika; A.A Ketut Budiastra (Universitas KH. Abdul Chalim Mojokerto, 2026)
Organizational output at the individual level can be interpreted as the extent to which employees convert entrusted roles into tangible contributions that reflect both effectiveness and productivity. In order to scrutinize the determinants of such output within FIFGROUP Denpasar, an empirical assessment was conducted involving the entire workforce population of 93 personnel through a full enumeration approach. The analytical framework positioned motivational drive, affective attachment to work, and behavioral compliance with organizational norms as explanatory dimensions, while individual output served as the focal outcome construct. Data were elicited using scaled attitudinal measures and examined through a multivariate regression procedure to estimate relational intensity among constructs. The statistical estimations indicate that each explanatory dimension independently demonstrates a meaningful positive association with individual output. When integrated simultaneously, these dimensions collectively account for a significant proportion of performance variation within the institutional setting.